The Effect of Various Concentrations of Telang Flower (Clitoria Ternatea L.) Extract on Cow Milk Yogurt Characteristic: Pengaruh Berbagai Konsentrasi Ekstrak Bunga Telang (Clitoria Ternatea L.) Terhadap Karakteristik Yogurt Susu Sapi - Chosyatillah, Annisa Alya; Saidi, Ida Agustini (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of the addition of butterfly pea flower extract (Clitorian Ternatea L.) on the characteristics of cow’s milk yogurt. The method used in this study was a randomized block design (RBD) using a single factor with 8 treatments repeated 3 times to obtain 24 experimental units. Data analysis was carried out using ANOVA and follow-up testing with a 5% level of Honest Significant Difference (SJL) and organoleptic test were analyzed using the Friedman test. The result showed that the additional og butterfly pea extract had no significant effect on the viscosity and pH of the cow’s milk yogurt, while on the color parameter the addition of the butterfly pea extract had avery significant effect on the characteristics of the cow’s milk yogurt. The result of this study showed that the highest value of the viscosity parameter was 68,2%, the lowest pH was 5,19%, the lowest lightness color value was 61,72%, the highest redness value was 4,07% and the lowest yellowness value was -21,46%.